Приключения Мохнатика и Веничкина - Кривошлыкова Светлана Алексеевна (Прикольные истории, 2018)
Экземпляры: ф.6 (20190731) / Инвентарный номер: 2883zzz / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 82 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-4